Penerapan Prinsip-Prinsip Murabahah dalam Perjanjian Islam - Lina Maulidiana (KEADILAN PROGRESIF, 2012)
Financial system and Islamic banking was part of economic concept of Islamic, which aimed to introduce value system and Islamic ethics in economical environment, because based of this ethics so financial and banking of Islamic to class moslem was not merely commercial transaction system, but looked from by many moslems circles as duty religion. Murabahah in Syariah Banking actually not limited marketing in customer that has religious emotional tie (moslem society). Syariah banking service could be enjoyed by everyone, did not depend on religion that professed, along ready to follow business manner that permitted according to syariah that is alliance did not contain gharar (indistinctness), maisir (gambling) and usury (interest)